Game Development for Fostering Smart Agricultural Innovators in Schools in Ban Phaeo District, Samut Sakhon Province - Nitivadee Pathep; Aungkarn Prinyachaisak; Waranan Isarapreeda (Utilitas Mathematica, 2025)
This research aimed to (1) develop educational games to cultivate smart agricultural innovators among secondary school students in Ban Phaeo District, Samut Sakhon Province, (2) assess the efficiency of these games in enhancing innovation in smart agriculture, and (3) evaluate students' innovative skills following game-based learning. The study involved four schools, targeting students aged 12–15, and employed the ADDIE Model with integrated Design Thinking to design two types of games: a digital game (Plug) and a board game (Farm Genius - Unplug).The findings revealed that both games demonstrated high efficiency in design and learning outcomes, with overall evaluation scores above 4.7 out of 5. After participation, students showed significant improvements in four key innovation skills: growth mindset, learning skills, financial literacy, and digital literacy. The average scores increased from 78.82 (Plug) to 95.94 (Farm Genius). These results highlight the games’ effectiveness in promoting creativity, problem-solving, and technological application, thereby supporting the development of future innovators in smart agriculture.